Utilization Of Banana Kepok As Active Charcoal For The Process Of Purification Of Used Cooking Oil Using The Adsorption Method - S Sariadi; Z Zulkifli; A Adriana; M Yunus; R Ridwan; S Salmyah; Een Setiawati; Isra Adelya Izzati (Politeknik Negeri Lhokseumawe, 2023)
Used cooking oil or often referred to as used cooking oil is one of the needs for food processing for humans. Repeated processing of cooking oil in the frying process can reduce the quality of the cooking oil. Therefore, one of the efforts to process used cooking oil is adsorption using activated charcoal from kepok banana peels. The use of activated charcoal as an adsorbent can be beneficial because activated carbon can absorb some unwanted odors and reduce the amount of free fatty acids, thereby improving the quality of the oil. The purpose of this study was to study the addition of the amount of kepok banana skin size of activated charcoal (mesh) with adsorption time on the quality of used cooking oil. The variables used were varying the size of the activated carbon particles of 100 mesh, 120 mesh, 140 mesh and 160 mesh with adsorption times of 3 hours, 5 hours and 7 hours. The refined oil will be analyzed for oil density, fatty acid content in the oil, and water content. From the research results it is known that the best particle size is 160 mesh. The density value is 0.889 g/ml. The results obtained are that the density value still does not meet the SNI (2002) cooking oil quality standard requirements, namely 0.900 g/ml. FTIR analysis shows that there is an increase in wave number which is the peak of the OH (hydrogen bond) structure using purified chorcoal. The C=O (carboxylate) FFA molecule is shown around the wave number 1060 cm-1 increasing to 1070 cm-1.Â Keywords: Adsorption, activated charcoal, kepok banana, free fatty acid (FFA), water content, density